(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study examines the alignment between the judge appointment system in the Religious Courts and the role of Sharia Faculties in preparing prospective judges, particularly regarding how well the competencies developed in higher education meet the requirements of a selection process that emphasizes integrity, legal capability, and practical skills. The study reviews the judge appointment mechanism, the contribution of Sharia Faculties in training prospective judges, and the various gaps that emerge between professional demands and the academic readiness of graduates. A descriptive-analytical method is employed through a literature review of judicial appointment regulations, academic sources, and recruitment documents. The findings show that although the judge selection system is based on merit and integrity, shortcomings remain in practical legal skills, mastery of procedural law, and ethical development within Sharia Faculties. These results highlight the need for strengthening the curriculum and expanding institutional collaboration to enhance graduate preparedness as candidates for judges in the Religious Courts.